Antimagicness for a family of generalized antiprism graphs - Dominique Buset; Mirka Miller; Oudone Phanalasy; Joe Ryan (Electronic Journal of Graph Theory and Applications (EJGTA), 2014)
An antimagic labeling of a graph $G=(V,E)$ is a bijection from the set of edges $E$ to the set of integers $\{1,2,…, |E|\}$ such that all vertex weights are pairwise distinct, where the weight of a vertex is the sum of all edge labels incident with that vertex. A graph is antimagic if it has an antimagic labeling. In this paper we provide constructions of antimagic labelings for a family of generalized antiprism graphs and generalized toroidal antiprism graphs.